If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + 6b + 7 + -2b = 1 + 5b Reorder the terms: 7 + 6b + -2b + -7x = 1 + 5b Combine like terms: 6b + -2b = 4b 7 + 4b + -7x = 1 + 5b Solving 7 + 4b + -7x = 1 + 5b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-5b' to each side of the equation. 7 + 4b + -5b + -7x = 1 + 5b + -5b Combine like terms: 4b + -5b = -1b 7 + -1b + -7x = 1 + 5b + -5b Combine like terms: 5b + -5b = 0 7 + -1b + -7x = 1 + 0 7 + -1b + -7x = 1 Add '-7' to each side of the equation. 7 + -1b + -7 + -7x = 1 + -7 Reorder the terms: 7 + -7 + -1b + -7x = 1 + -7 Combine like terms: 7 + -7 = 0 0 + -1b + -7x = 1 + -7 -1b + -7x = 1 + -7 Combine like terms: 1 + -7 = -6 -1b + -7x = -6 Add '7x' to each side of the equation. -1b + -7x + 7x = -6 + 7x Combine like terms: -7x + 7x = 0 -1b + 0 = -6 + 7x -1b = -6 + 7x Divide each side by '-1'. b = 6 + -7x Simplifying b = 6 + -7x
| sin^3(4x)=1 | | 7p+5=6p+8 | | 42=2f-3 | | 5(3x-2)=45 | | 3x+y-z=15 | | (x)+(2x+4)+(2x-9)=180 | | 0.25y-6=9 | | -8x+2=10 | | 4x-15=69 | | 5=-3x-4 | | f(x)=3(x-5)+4 | | x-(-2)=-2 | | 5a=45+29 | | 40160*x=8x-1600 | | 3x+6y=360 | | 4x+8+2x-9=14 | | 12y+5[y-6]=4 | | t^2+9t+14= | | 4x-4=3.75 | | 3-2t=7+4 | | -5.6+-0.8y-y=-2 | | x+6+x+3+x+9+x+1+x+1+x+4+x+4= | | 0.5x-3=0.3(2x-3) | | -4.7k=10.81 | | x(13)=104 | | x(5)=55 | | 7t-2(-3t+1)=-3(1-3t) | | 8m-10=62+2m | | -11x+9=185 | | x+2(2)=0 | | 6d+5=-4-3d | | X+(x-355)+(2x+80)=2425 |